Funcionalidad familiar y habilidades sociales en el retorno a la educación presencial de los adolescentes. I.E. N0 88046 José Carlos Mariátegui - Chimbote - Paredes Angulo, Brenda Elizabeth (2023)
The objective of this study is to analyze the influence of family functionality on the development of adolescents' social skills in the return to face-to-face education of the I.E. N0 88046 José Carlos Mariátegui- Chimbote, considering as a sample universe 52 families with adolescents from 4th and 5th grade of secondary level. The development of the research shows an inductive-deductive approach and a statistical method, in which a David Olson scale was applied to measure family cohesion and adaptation called Faces III and the evaluation list of social skills developed by the Ministry of Health in the year 2005. Concluding that the influence of family functionality in the development of social skills of adolescents in the return to face-to-face education is significant; where 67.3% of families with adolescents are in the middle range in terms of their functionality with a separation-type cohesion and a chaotic-type adaptation; which determines a deficit in the low average development of social skills such as: communication, assertiveness, decision making and self-esteem; affecting the bond of adolescents with their family circle and with their peers.